DINAMIKA PERIBADATAN GEREJA INJILI DI INDONESIA PASCA KONFLIK TOLIKARA: STUDI KASUS DI DESA MOJOKERTO KECAMATAN KEDAWUNG SRAGEN - MUSTOLEHUDIN MUSTOLEHUDIN (Jurnal Dialog, 2017)
Evangelical church named Gereja Injili in Indonesia (GIDI) has been established in Sragen since 1990. Sinceits establishment to the mid-2015, there has been no significant disagreement with the local people. A frictionappeared shortly after Tolikara conflict in July 2015. By employing a qualitative approach, this study finds outthat: first, GIDI in Sragen has not obtained a juridical license according to Joint Ministerial Regulations (PBM)No. 8 and 9 2006. Second, the accusation of Surakarta Muslim Troops (Laskar Umat Islam Surakarta) that GID I created disharmony in the society was proven not true. The church committee maintained a good cooperation with local society in terms of helping them during their celebration ceremonies. KEY WORDS: GID I Sragen, House of Worship, LUIS, FKUB